On Religious Skepticism - Schellenberg, J. L. (International journal for the study of skepticism, 2020)
Abstract I seek to promote a fuller understanding of religious skepticism by defending five theses. These concern, respectively: its breadth, discussed in relation to theism on the one hand and naturalism on the other; why it should be distinguished from a general metaphysical skepticism; how it is supported by the consequences of recent cultural evolution, which at the same time enable new and stronger arguments for atheism; the relations it bears to non-doxastic religious faith; and, finally, its curious capacity in certain not uncommon circumstances to take the form of a soft irreligion that is widely approvable—even from a religious perspective.